Official language knowledge among foreign-born immigrants in Catalonia, Spain, and implications for their social integration - Solana, Miguel; de Miguel Luken, Verónica; Rodríguez García, Dan; Pascual de Sans, Àngels (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
In recent years, Catalonia has experienced asignificant in flux of international immigrants, added to the already important internal migration flows of prior decades. Now, however, this immigration takes place in a political and social context in which Catalan is the language of official use in all branches of government administration as well as in the education system. Knowledge of the Catalan language has been consideredan essential part of the process of integration for the immigrant population residing in Catalonia. Using the data provided by therecent 2007 National Survey of Immigrants, this article analyzes the immigrant population’s knowledge of Catalan in relation totheir knowledge of Castilian (Spanish). The data indicates that inspite of the offi cial status of the Catalan language in Catalonia,knowledge of Catalan among immigrants to the region is relatively low and much lower than that of Castilian, a situation that invitesrefl ection on the social implications of this reality.
Keywords: Catalonia; Language; Catalan; Integration; Immigration.